Straight proximal humeral nailing: Risk of iatrogenic tendon injuries with respect to different entry points in anatomical specimens. Issue 10 (October 2018) - Schwarz, A.M.; Hohenberger, G.M.; Euler, S.; Weiglein, A.H.; Riedl, R.; Kuchling, S.; Krassnig, R.; Plecko, M.
Abstract: Background: The purpose of the study was to evaluate the relationship of implant-related injuries to the adjacent anatomical structures in a newer generation straight proximal humeral nail (PHN) regarding different entry points. The proximity of the proximal lateral locking-screws of the MultiLoc proximal humeral nail (ML PHN) may cause iatrogenic tendon injuries to the lateral edge of the bicipital humeral groove (BG) as reference point for the tendon of the long head of biceps brachii (LBT) as well as the lateral insertion of the infraspinatus tendon (IST). Materials and methods: The study comprised n = 40 upper extremities. Nail application was performed through a deltoid approach and supraspinatus tendon (SSP) split with a ML PHN. All tests were performed in three different entry points. First nail (N1) – standard position in line with the humeral shaft axis; second nail (N2) – a more lateral entry point; third alternative (N3) – medial position, centre of the humeral head. After nail placement, each specimen was screened for potential implant-related injuries or worded differently hit rates (HR) to the BG and the IST. The distances to the anatomical structures were measured and statistically interpreted. Results: The observed iatrogenic IST injury rate was 17.5% (n = 7/40) for N1, 5% (n = 2/40) for N2 and 62.5% (n = 25/40) for N3, which was statistically significantly higher (p < 0.001). Regarding the BG, the evaluated HR was 7.5% (n = 3/40) for both N1 and N2. Only the nail placed in the head centre (N3) showed an iatrogenic injury rate of 20% (n = 8/40) (p < 0.062). No statistically significant association between humeral head size and the HR could be observed (head diameter: IST: p = 0.323, BG: p = 0.621; head circumference: IST: p = 0.167; BG: p = 0.940). For the IST and BG, all distances in nail positions N1 and N2 as well as N2 and N3 differ statistically significant (p < 0.001). Conclusions: An entry point for nail placement in line or slightly laterally to the humeral shaft axis – but still at the cartilage – should be advocated.